(untitled) (CAHIERS MAGELLANES-NS, 2024)
Objective: In 2020, breast cancer was ranked as the fifth leading cause of cancer-related deaths globally. One of the most prevalent cancers worldwide is the breast cancer. According to the International Agency for Research on Cancer, there were over 2.26 million new breast cancer cases and approximately 685,000 deaths globally. [1] Researchers in Saudi Arabia have been actively contributing to breast cancer research, publishing numerous studies. [2] A systematic analysis of these publications is essential to understand the current landscape and guide future breast cancer research policies in Saudi Arabia. Methodology: The search query used for this study included: “Breast cancer” OR “cancer in women” OR “breast premalignant lesion” OR “Potentially malignant disorder” AND AFFIL (Saudi AND Arabia). Articles were retrieved from the PubMed Central database, and various bibliometric tools within PubMed were used to analyze key metrics. The search yielded a total of 2,482 journal articles related to the query. Most of these publications originated from King Saud University (1,330), followed by King Abdulaziz University (560), King Faisal Specialist Hospital and Research Centre (213), and King Saud University College of Applied Medical Sciences (108). Conclusion: Saudi researchers are actively addressing the public health challenge posed by breast cancer. However, the analysis revealed that a few institutions are leading in research output, while contributions from others remain limited. To enhance breast cancer research efforts, the health department should take proactive steps to encourage greater participation from a wider range of institutions. Evidence from the research indicates that the disease has been more prevalent over the last 20 years, highlighting the need to raise community awareness about breast cancer prevention measures.